DOES SHORT TERM DEBT AFFECT PROFITABILITY? EVIDENCE FROM THE ROMANIAN LISTED COMPANIES - MILOŞ LAURA RAISA; MILOŞ MARIUS CRISTIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
This study aims at providing new empirical evidence on the influence of debt (both on short and long term) on corporate profitability, with application to the Romanian companies listed on the Bucharest Stock Exchange. Panel data are analyzed for 50 companies belonging to different fields of activity during 2003-2014 using a fixed effect regression model. After we control for size, growth, liquidity, and tangibility of assets, the results reveal that short-term debt has a negative influence on corporate profitability.